CHILDREN CHARACTER DEVELOPMENT THROUGH NON-FORMAL AND INFORMAL EDUCATION IN “KRAMBIL” CHILDREN’S HOME OF READING AND CREATIVE STUDIO COMMUNITY - Efiyanti, Alfiana Yuli (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
The development of children's character becomes urgent considering that children are a part of young generation who will undertake the nation’s future. Education process is one of the best way to develop children’s character. The process can be carried out through formal, non-formal or informal education. Based on a research using descriptive qualitative approach, it is known that the efforts of “Krambil” Children’s Home of Reading and Creative Studio community to characterize children who come from lower-middle class in Blimbing, Malang through non-formal and informal education. Through literacy or reading activities, children are encouraged to develop their knowledge by analyzing the author’s idea. In addition to reading, children are also invited to understand and love Indonesian culture through various artistic activities, such as dancing, singing, storytelling and creating dances and composing songs. Children also gain an environment to develop creativity based on their talents and interests. Accompanied by the founder of that community in most activities, some characters have been established by “Krambil” Children’s Home of Reading and Creative Studio. The most prominent character is the creativity. In addition, other characters also exist, such as selfconfidence, gratefulness, discipline and so on.